2019
DOI: 10.1111/bjh.16179
|View full text |Cite
|
Sign up to set email alerts
|

International external quality assessment for measurements of direct oral anticoagulants: results and recommendations

Abstract: There is limited information regarding the performance of tests for direct oral anticoagulants (DOACs). To generate more knowledge, the accuracy of DOAC tests were evaluated using external quality assessment data from multiple years. This data demonstrated a good correlation for the tests with a small overall interlaboratory variability (10% for dabigatran, rivaroxaban and apixaban and 12% for edoxaban). The greatest differences between the various reagents were observed for rivaroxaban, especially for concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Most international external quality control (EQA) programmes now have established EQA exercises for DOACs and demonstrate a wide implementation of specific DOAC testing in certain regions of the world. [111][112][113][114][115][116][117][118] Nevertheless, in regions where the regulatory authorities have refused the approval of these specific kits, access to drug measurements may be limited to specialized laboratories. In addition, only few undertake the in-house validation of these techniques refraining the clinicians to ask for these specific drug measurements.…”
Section: External Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Most international external quality control (EQA) programmes now have established EQA exercises for DOACs and demonstrate a wide implementation of specific DOAC testing in certain regions of the world. [111][112][113][114][115][116][117][118] Nevertheless, in regions where the regulatory authorities have refused the approval of these specific kits, access to drug measurements may be limited to specialized laboratories. In addition, only few undertake the in-house validation of these techniques refraining the clinicians to ask for these specific drug measurements.…”
Section: External Quality Controlmentioning
confidence: 99%
“…6,119 Some international EQA programmes have also undertaken and published studies looking at DOAC interference in haemostasis tests. [111][112][113][114][115][116][117][118] Some have also undertaken studies looking at neutralizing the interference of DOACs in haemostasis tests. 120 Although differences were seen between the various methodologies, reliable and reproducible DOAC levels were measured overall.…”
Section: External Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the higher number of participants, they were able to evaluate the data per reagent group if more than 10 participants were present in the survey from 2017. 24 Another ECAT international dabigatran and rivaroxaban survey with a large number of international participants and a small percentage of North American laboratories (11 of 123) assessed the interlaboratory variation by using the same definition 14 and showed similar findings 25 : intermediate CV for the 2 most commonly used dabigatran assays (dTT, Hemoclot; and anti-IIa assay, Biophen DTI). Owing to the large number of participants, they were able to sort the data by reagents and calibrators.…”
Section: The Performance Of Direct Oral Anticoagulant Assaysmentioning
confidence: 95%
“…The previously mentioned first ECAT study's lowest rivaroxaban concentration of 85 ng/mL had an overall CV of 13%, which differed significantly between different methodologies (up to 20% difference), with the lowest CV observed for Stago and HemosIL Liquid Anti-Xa assays. 24 The second ECAT study assessed 2 rivaroxaban concentrations (100 ng/mL and 300 ng/mL) and showed that 5 of the 6 most commonly used reagents had intermediate interlaboratory precision (11%-20%) for 100ng/mL drug concentration. 25 These results suggest that interlaboratory variability for dabigatran and rivaroxaban measurement could be improved.…”
Section: The Performance Of Direct Oral Anticoagulant Assaysmentioning
confidence: 99%